Analysis of Factors Affecting the Productivity of Smallholder Tea Farming in Solok Regency, West Sumatra - Uci Sarly Riani; Hasnah Hasnah; Ira Wahyuni Syarfi (Universitas Andalas, 2022)
This study aims to analyze the factors affecting the productivity of smallholder tea farming in Solok Regency. Sixty-five tea farmers, selected using a simple random sampling approach, were involved in this study. The study reveals that urea fertilizer, SP-36 fertilizer, insecticides, labor, plant age, and seedling varieties significantly affect tea yield at the level of α = 0.10. Farmers can increase the yield of tea farming by increasing fertilizer and labor and intensive pest and disease control. Gambung variety produces a higher yield than TRI, and the yield increases with the age of the plant.